Ligamentum teres lesions are associated with poorer patient outcomes in a large primary hip arthroscopy cohort of 1,935 patients - Perumal, Vivek (2022)
Purpose: To retrospectively evaluate the prevalence and characteristics of ligamentum teres (LT) lesions identified in a single-surgeon hip arthroscopy cohort and to compare surgical outcomes of those with, and without, identified LT lesions. Methods: Patients who underwent primary hip arthroscopy between 2005 and 2018 in one surgeon's clinic were identified. Those with a history involving extra-articular scoping or any previous surgery on the ipsilateral hip were excluded. Patient-reported outcome measures completed before and after surgery included the Hip Disability and Osteoarthritis Outcome Score, Nonarthritic Hip Score, and 12-item International Hip Outcome Tool. Conversion to hip joint replacement was ascertained through a national register. Results: A total of 1,935 primary hip arthroscopies (from 1,607 different patients) were included in this study. In total, 323 LT lesions were identified. Those with LT lesions were older than those without (40.3 ± 11.3 years compared with 33.9 ± 12.1 years; P < .001), and more frequently female (58.2% vs 41.8%; P = .001). Hips with lesions had a smaller lateral center-edge angle than other hips (33.0 ± 6.8° vs 34.1 ± 6.0°; P = .004). All patient-reported outcome measures improved significantly (P < .001) from pre- to post-surgery for patients with and without LT lesions. However, patients with LT lesions reported less improvement in the 12-item International Hip Outcome Tool (difference –5.60; P = .004) and in Hip Disability and Osteoarthritis Outcome Score symptoms (–4.41; P = .004), sports (–7.81; P < .001), and quality of life subscales (–8.85; P < .001) than those without lesions. Hips with LT lesions also had a 6.2% 2-year rate of subsequent hip replacement (20/323 hips) compared with those without lesions (0.9%; 14/1612 hips; P < .001). Conclusions: In this single-surgeon hip arthroscopy cohort, identification of LT lesions was associated with poorer patient-reported outcomes and increased likelihood of conversion to arthroplasty within 2 years. These findings suggest a poorer prognosis for patients with LT injury compared with those without. Level of Evidence: Level III, retrospective cohort study.